1999
DOI: 10.2466/pr0.1999.85.2.497
|View full text |Cite
|
Sign up to set email alerts
|

Intimacy, Passion, and Commitment in Young Romantic Relationships: Successfully Measuring the Triangular Theory of Love

Abstract: The previous tests of the Triangular Theory of Love have proven problematic, specifically centered on measurement of the three components of Intimacy, Passion, and Commitment. Factor analysis of a new set of measures for 123 women and 110 men indicated support for three distinct factors. Sex differences indicated that women scored significantly higher on Intimacy and Commitment than men. Components were also significantly related to a measure of Relational Satisfaction. Regression analysis indicated that each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 10 publications
2
29
0
5
Order By: Relevance
“…Adapted Triangular Love Scale (Lemieux & Hale, 1999) This is a 9-item adaptation of Sternberg's (1998) original measure and a later adaptation by Lemieux and Hale. The scale accesses three components of love, namely intimacy, passion, and commitment.…”
Section: Methodsmentioning
confidence: 99%
“…Adapted Triangular Love Scale (Lemieux & Hale, 1999) This is a 9-item adaptation of Sternberg's (1998) original measure and a later adaptation by Lemieux and Hale. The scale accesses three components of love, namely intimacy, passion, and commitment.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, our aim is to explore whether there are differences per stage. Using psychological theory, we will distinguish between 'getting acquainted', 'in love', 'courtship', 'living together', 'several years of marriage', 'marital' and 'divorce' (Lemieux and Hale, 1999, 2002. These stages mimic to some extent the stages as described by Dwyer et al (1987), where customers move from awareness ('getting acquainted'), exploration ('courtship'), expansion ('living together'; 'just married'), commitment ('several years of marriage') to dissolution ('divorce').…”
Section: Customer Lifecyclementioning
confidence: 99%
“…Lemieux and Hale (1999) found passion and intimacy to be stronger than commitment in young dating adults. The current research found that the enamored in all five types of UL relationships reported less intense positive feelings than did those in equal love relationships (Hill et al, 1997, did not report results on intensity).…”
Section: Discussionmentioning
confidence: 93%